2018
DOI: 10.1177/1455072518803281
|View full text |Cite
|
Sign up to set email alerts
|

The association between social characteristics, alcoholic beverage preferences, and binge drinking in a Serbian adult population

Abstract: Aim: To determine the association of sociodemographic characteristics and type of alcoholic beverage consumed during binge drinking in Serbia. Method: We conducted a secondary analysis of data from the 2014 national survey on Serbian lifestyles focusing on substance abuse and gambling. The sample consisted of 5385 individuals. The respondents were divided into non-binge drinkers and binge drinkers, according to the quantity of alcohol consumed during one occasion. Binge drinkers reported consuming more than 60… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 44 publications
2
11
0
1
Order By: Relevance
“…Consistent with previous research findings [6][7][8]12,17,22], this study found strong associations between past and current smoking with HED. Reasons for this may lie in the co-dependence risk of HED and nicotine [40].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Consistent with previous research findings [6][7][8]12,17,22], this study found strong associations between past and current smoking with HED. Reasons for this may lie in the co-dependence risk of HED and nicotine [40].…”
Section: Discussionsupporting
confidence: 92%
“…In addition, sexstratified multivariable logistic regression models with HED prevalence were calculated. Based on a previous literature review [5][6][7][8]12,16,17,[19][20][21][22][23][24][25][26][27][28][29][30][31], covariates included sex, age group, highest level of education, ethnicity, smoking status, obesity, fruit and vegetable intake, physical activity, sedentary behaviour and health care utilization. Taylor linearization methods were applied to account for the complex study design and the sampling weight.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly to previous research studies, this study showed that men in Serbia and Hungary are more likely to consume alcohol compared to women, which can be related not only to the cultural heritage and the generally accepted model of behaviour, but also to the greater economic power of men. Evidence suggests that the gender gap in socio-economic status is significant between the two countries [26][27][28][29][30].…”
Section: Discussionmentioning
confidence: 99%
“…School survey data are used in the study by Karlsson, Ekendahl, Månsson, and Raninen (2019) to investigate whether illicit drug use has become normalised in groups of Swedish youth. In an article by Pakovic, Todorovic, Santric-Milicevic, Bukumiric, and Terzic-Supic (2019) attention is turned to a Serbian adult population looking for associations between social characteristics, alcoholic beverage preferences, and binge drinking. Last but not least, the fourth article of this issue concerns the alcohol-use context of Swedish student unions – an interesting study environment, when following up the decreased alcohol consumption trend among Nordic teenagers ( Strandberg, Elgán, Jägerskog, & Gripenberg, 2019 ).…”
Section: Vulnerable Groupsmentioning
confidence: 99%